2019
DOI: 10.29252/ibj.23.5.2
|View full text |Cite
|
Sign up to set email alerts
|

Novel Poly(Adenosine Diphosphate-Ribose) Polymerase (PARP) Inhibitor, AZD2461, Down-Regulates VEGF and Induces Apoptosis in Prostate Cancer Cells

Abstract: Background: Prostate cancer (Pca) is a heterogeneous disease, and current treatments are not based on molecular stratification. Poly(adenosine diphosphate [ADP]-ribose) polymerase (PARP) inhibitors have recently been found to be remarkably toxic to cells with defects in homologous recombination, particularly cells with BRCA-mutated backgrounds. Therefore, this preliminary study was designed to evaluate whether PTEN expression status could have an impact on the sensitivity of invasive Pca cells to the PARP inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…We also detected the tumor metastasis–related matrix metalloproteinases (MMPs) and found that adenosine increased MMP-2, MMP-7, MMP-9, and MMP-13 expression in the MKN45 cells, but that SCH 58261 blocked this effect (Figure 2D). However, the expression of MMP9, 48 h and 72 h decreased slightly more than 24 h, which may be related to adenosine-induced tumor cell apoptosis (Sargazi et al , 2019; Soleimani et al , 2019). Collectively, these findings demonstrate that adenosine promotes tumor invasion and metastasis in GC through the A2aR pathway.…”
Section: Resultsmentioning
confidence: 93%
“…We also detected the tumor metastasis–related matrix metalloproteinases (MMPs) and found that adenosine increased MMP-2, MMP-7, MMP-9, and MMP-13 expression in the MKN45 cells, but that SCH 58261 blocked this effect (Figure 2D). However, the expression of MMP9, 48 h and 72 h decreased slightly more than 24 h, which may be related to adenosine-induced tumor cell apoptosis (Sargazi et al , 2019; Soleimani et al , 2019). Collectively, these findings demonstrate that adenosine promotes tumor invasion and metastasis in GC through the A2aR pathway.…”
Section: Resultsmentioning
confidence: 93%
“…The previous study has shown that PARP activity is necessary for repairing single-strand DNA breakage [32]. Therefore, inhibition of PARP function can lead to apoptosis of homologous recombinant tumor cells [33]. PARP inhibitors are the biggest advance in the treatment of OC in recent years [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that in tumors, PARPi had anti-angiogenesis potential through suppressing VEGFa expression. 28,43 CD31 is known as a platelet-endothelial cell adhesion molecule and is expressed on the surface of vascular endothelial cells. Our results showed that CD31 + cells were decreased in tumor tissue after the combined therapy compared with the CAR-T cell treatment alone (Figures 3J and 4J), suggesting the combined therapy has an anti-angiogenesis capacity.…”
Section: Discussionmentioning
confidence: 99%